Key Frame Extraction Method for Minors’ Participation in Online Short-Form Video from the Perspective of Government Administration - Qiuli Wu (Discrete Dynamics in Nature and Society)
With the progress of the Internet era, the audience scope of online short-form video and live broadcast platform is rapidly expanding. In this situation, the physical and mental health of minors is affected and harmed, and serious social problems have been caused. In view of the random images of minors participating in short online videos, the monitoring department should strengthen supervision and control and establish a good network atmosphere. The focus of surveillance is to identify short-form videos in which minors participate, monitor the content of short-form videos, and effectively identify minors. On the basis of analyzing and studying the existing methods of moving object extraction, the method of spatio-temporal information combined with geometric curve evolution is used to improve the effect of moving object extraction. Firstly, the time dynamic information of video frames is fully utilized and the initial contour of the target is segmented by high-order statistical algorithm. Based on the improved watershed algorithm, the spatial frames of the original image are segmented and the secondary contour of the target is obtained by combining the spatial and temporal information. The level set evolution algorithm is used to remove the noise and information void in the secondary target, and the final moving target is obtained. Through the extraction of key frames, it can effectively control the appearance of minors in short-form videos, which can actively guide the benign development of the platform, and put forward governance suggestions based on the perspective of government management.